Serum IL-18 Is Closely Associated with Renal Tubulointerstitial Injury and Predicts Renal Prognosis in IgA Nephropathy - Beili Shi; Zhaohui Ni; Liou Cao; Minjie Zhou; Shan Mou; Qin Wang; Minfang Zhang; Wei Fang; Yucheng Yan; Jiaqi Qian (Hindawi Limited, 2012)
Background. IgA nephropathy (IgAN) was thought to be benign but recently found it slowly progresses and leads to ESRD eventually. The aim of this research is to investigate the value of serum IL-18 level, a sensitive biomarker for proximal tubule injury, for assessing the histopathological severity and disease progression in IgAN. Methods. Serum IL-18 levels in 76 IgAN patients and 36 healthy blood donors were measured by ELISA. We evaluated percentage of global and segmental sclerosis (GSS) and extent of tubulointerstitial damage (TID). The correlations between serum IL-18 levels with clinical, histopathological features and renal prognosis were evaluated. Results. The patients were 38.85±10.95 years old, presented with 2.61 (1.43∼4.08) g/day proteinuria. Serum IL-18 levels were significantly elevated in IgAN patients. Baseline serum IL-18 levels were significantly correlated with urinary protein excretion (r=0.494, P=0.002), Scr (r=0.61, P<0.001), and eGFR (r=−0.598, P<0.001). TID scores showed a borderline significance with serum IL-18 levels (r=0.355, P=0.05). During follow-up, 26 patients (34.21%) had a declined renal function. Kaplan-Meier analysis found those patients with elevated IL-18 had a significant poor renal outcome (P=0.03), and Cox analysis further confirmed that serum IL-18 levels were an independent predictor of renal prognosis (β=1.98, P=0.003).